Ibnu Ashur's Interpretation On Qs. An-Nahl Verse 78 Regarding The Character Building Of Prenatal Children - Muhammad, Hafid Nur; Mahdhor, Muslich Marzuki; Famela, Sidney (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Prenatal character building reflects the importance of educating children well. Character education can start from the prenatal period in accordance with the Qur'anic verse in QS. Al-A'raf verse 172 which tells the story of fetal interaction with God during the allegiance. Although there is a view that prenatal children cannot be educated on the grounds of the verse QS. An-Nahl verse 78, but learning potential such as hearing and vision can be started early. This research studies the pattern of character building of prenatal children based on the perspective of tafsir at-tahrir wa at-tanwir by Ibn Ashur and its application in society. This research method is a literature study with a descriptive approach of tarbawi interpretation to understand the context of QS. The character building of prenatal children is directed to optimize the potential of as-sam'a, al-abshar, and al-af'idah as mentioned in QS. This involves the coordination of these three potentials to understand the science and nature of things so that children understand the right way to live. Based on the author's analysis, character education methods for prenatal children must pay attention to fundamental values such as al-fitrah, al-samahah, al-musawah, and al-huriyyah by using appropriate methods such as prayer, worship, reading, dhikr, dialogue, joint activities, and naturally conducive methods.